Physical Exercise During Pregnancy – How Active Are Pregnant Women in Germany and How Well Informed? - Schmidt, Thorsten; Heilmann, Thorsten; Savelsberg, Luisa; Maass, Nicolai; Weisser, Burkhard; Eckmann-Scholz, Christel (Geburtshilfe und Frauenheilkunde, 2017)
Introduction There is sufficient evidence showing the positive effects of physical exercise on various aspects of pregnancy. This study evaluates knowledge and status of physical exercise among pregnant women. Methods The standardised paper-pencil questionnaire “Pregnancy Physical Activity Questionnaire” (PPAQ) as well as general demographic questions were used to assess the exercise behaviour of study participants. 83 questionnaires completed by women presenting to the Kiel University Hospital for antenatal assessment were included in the analysis. Results At the time of questionnaire completion 10 women were in the first trimester of pregnancy, 64 in the second, and 9 in the third. Just less than 90% of participants felt they had been informed “sufficiently” on the topic physical exercise during pregnancy, over 50% felt they were “well” or “very well” informed. Just less than half of participants received their information from a doctor (either their gynaecologist or general practitioner) and none of these felt “insufficiently” informed. Almost 80% of participants reported still doing no sport or less exercise than before falling pregnant. The maximum proportional energy expenditure for recreational activity – just under 20% – was in the third trimester. Women who felt they had been well counselled tended to have higher activity levels. Conclusion Study participants demonstrated a clear decline in physical exercise during pregnancy despite clear evidence of the benefits of regular exercise for pregnant women, and despite participants feeling they were well informed. Detailed information on the recommendations for physical exertion in pregnancy should form an integral part of antenatal counselling.Einleitung Die positiven Effekte einer körperlichen Aktivität auf verschiedene Bereiche der Schwangerschaft sind hinreichend belegt. Die vorliegende Arbeit untersucht den Informationsstand von Schwangeren zum Thema Bewegung und körperliche Aktivität sowie deren Aktivitätsstatus während der Schwangerschaft. Methoden Als Erhebungsinstrumente zur Bestimmung des Aktivitätsverhaltens von Schwangeren dienten der vollstandardisierte Paper-Pencil-Fragebogen Pregnancy Physical Activity Questionnaire (PPAQ) sowie allgemeine Fragen zur Person. 83 Fragebögen wurden von Schwangeren, die sich im Rahmen einer Pränataldiagnostik am Universitätsklinikum in Kiel vorstellten, bei der Auswertung berücksichtigt. Ergebnisse 10 Schwangere wurden im 1., 64 Schwangere im 2. und 9 Schwangere im 3. Trimenon befragt. Knapp 90% der Teilnehmerinnen fühlten sich zumindest „zufriedenstellend“ über das Thema Bewegung während der Schwangerschaft informiert, über 50% sogar „gut“ oder „sehr gut“. Nur knapp die Hälfte der Teilnehmerinnen hat durch den Gynäkologen oder Hausarzt Informationen erhalten, keine der Schwangeren fühlte sich nach einer ärztlichen Beratung „ungenügend“ informiert. Knapp 80% der Teilnehmerinnen gaben an, weiter keinen oder weniger Sport zu machen als vor der Schwangerschaft. Der maximale anteilige Energieverbrauch durch die Aktivität in der Freizeit ergab sich mit knapp 20% für das 3. Trimenon. Teilnehmerinnen, die sich gut beraten fühlten, hatten tendenziell höhere Aktivitätslevel. Schlussfolgerungen Trotz einer eindeutigen Datenlage zum Nutzen regelmäßiger körperlicher Aktivität in der Schwangerschaft und einem subjektiv als hoch empfundenen Informationsgrad muss ein deutlicher Rückgang der körperlichen Aktivität der Teilnehmerinnen in der Schwangerschaft konstatiert werden. Eine differenzierte Beratung über die Empfehlung zur körperlichen Belastung sollte elementarer Bestandteil der ärztlichen Beratung sein.
Keywords: pregnancy; physical exercise; sport; information; counselling